The Influence Of Facilities, Prices, And Taste On Customer Satisfaction (Survey On Cafe Naw-Naw Tasikmalaya Consumers) - Dinda Anjani; Budhi Wahyu Fitriadi; Rita Tri Yusnita (Universitas Dehasen Bengkulu, 2023)
The purpose of this study is to determine the effect of facilities, prices, and taste on consumer satisfaction of Naw – Naw Tasikmalaya coffee. The research method used is a quantitative method with a survey approach to 100 respondents who are consumers of Naw-Naw coffee. The types of data used are primary data and secondary data. The data analysis technique used is multiple regression analysis. The results of this test prove that facilities, prices, and tastes have a significant effect both partially and simultaneously on consumer satisfaction of Naw – Naw Tasikmalaya coffee.